The Underlying Mechanism of 3-Hydroxyphthalic Anhydride-Modified Bovine Beta-Lactoglobulin to Block Human Papillomavirus Entry Into the Host Cell - Hua, Chen; Zhu, Yun; Wu, Congquan; Si, Lulu; Wang, Qian; Sui, Long; Jiang, Shibo (Frontiers in Microbiology, 2019)
We have previously demonstrated that 3-hydroxyphthalic anhydride (3HP)- modified bovine beta-lactoglobulin (3HP-β-LG) is highly effective in inhibiting in vitro infection by pseudovirus (PsV) of high- and low-risk human papillomavirus (HPV). Intravaginally applied 3HP-β-LG-containing vaginal gel could significantly inhibit HPV infection and reduce viral load in the cervical region. However, we still do not understand the underlying molecular mechanism by which 3HP-β-LG is able to inhibit HPV infection. Here, though, we showed that 3HP-β-LG did not inactivate HPV PsV, but rather blocked entry of HPV PsV into the target cell via its interaction with virus, not cell. It bound to the positively charged region in the HPV L1 protein, suggesting that 3HP-β-LG binds to HPV L1 protein through the interaction between the negatively charged region in 3HP-β-LG and the positively charged region in HPV L1 protein, thus competitively blocking the binding of HPV to the receptor on the basement membrane in vaginal mucosa. Although 3HP-modified chicken ovalbumin (3HP-OVA) also carries high net negative charges, it exhibited no anti-HPV activity, suggesting that the interaction between 3HP-modified protein and HPV L1 protein relies on both electrostatic and matchable conformation of the binding sites in both proteins. When topically applied, 3HP-β-LG did not enter the host cell or blood circulation.These findings suggest that 3HP-β-LG targets HPV L1 protein and blocks HPV entry into the host cell, thus being safe and effective for topical application in the treatment of HPV infection.